2023
DOI: 10.30737/ukarst.v7i1.4318
|View full text |Cite
|
Sign up to set email alerts
|

Grid Satellite Rainfall Products Potential Application for Developing I-D and E-D Thresholds for Landslide Early Alert System over Bali Island

Abstract: Bali has been one of the most popular tourist destinations in Indonesia. However, on the other hand, Bali has a high risk of natural disaster vulnerability. The number of landslides in Bali took the first position compared to other natural disasters. Currently, remote sensing platforms can present Grid Satellite Rainfall Products (GSRPs), which provide rainfall information that can identify rainfall conditions for landslide events. This study aims to analyze the potential GSRPs application of Precipitation Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Cumulative rainfall estimation by PERSIANN yields a robust correlation with rainfall stations, whereas IMERG and GSMaP exhibit instances of overestimation and underestimation. Notably, IMERG presents minimal deviation when gauging accumulated rainfall that triggers landslide events in comparison to other datasets [21]. Further analysis reveals IMERG's proficiency across daily, decadal, and seasonal time scales, while GSMaP displays a negative bias across all observed scales (daily, decadal, monthly, and seasonal) [17].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Cumulative rainfall estimation by PERSIANN yields a robust correlation with rainfall stations, whereas IMERG and GSMaP exhibit instances of overestimation and underestimation. Notably, IMERG presents minimal deviation when gauging accumulated rainfall that triggers landslide events in comparison to other datasets [21]. Further analysis reveals IMERG's proficiency across daily, decadal, and seasonal time scales, while GSMaP displays a negative bias across all observed scales (daily, decadal, monthly, and seasonal) [17].…”
Section: Introductionmentioning
confidence: 83%
“…A number of researchers have tried to establish rainfall thresholds in accurately predicting slope collapse/landslide using the parameters of average rainfall, duration of the rainfall event, a ratio of rainfall to daily rainfall, previous rainfall to annual average rainfall, and daily rainfall to maximum previous rainfall ratio [2], [23]- [28]. The utilization of satellite rainfall products in determining the rainfall threshold for landslide occurrence is still little done especially in Bali Province [21]. Previous researchers have analyzed many landslide-triggering rainfall events for the determination of rainfall threshold values using daily, dasarian, and monthly rainfall data [6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scholars have conducted prior research to investigate the utilization of satellite-derived precipitation data in the determination of rainfall thresholds that trigger landslides. Prominent studies have examined the contributions of TRMM [15], [18]- [20], GSMaP [21], [22], IMERG [11], [18], [22]- [24], PERSIANN [12], [22], and CMOPRH [9]. Previous studies have identified variations in the effectiveness of SRGDs, which can be attributed to regional factors.…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved by considering parameters such as average rainfall, the duration of rainfall events, the ratio of rainfall to daily rainfall, previous rainfall to average annual rainfall, and daily rainfall to the maximum ratio of previous rainfall [1], [4]- [9], [27]. The utilization of SRGDs in determining rain thresholds for landslide events is still limited, especially in Bali Province [22]. Moreover, previous studies have not analyzed rainfall thresholds based on the integration of high temporal-spatial resolution of SRGDs.…”
Section: Introductionmentioning
confidence: 99%